MicroRNA Variants and HLA-miRNA Interactions are Novel Rheumatoid Arthritis Susceptibility Factors - Guo, Shicheng; Jin, Yehua; Zhou, Jieru; Zhu, Qi; Jiang, Ting; Bian, Yanqin; Zhang, Runrun; Chang, Cen; Xu, Lingxia; Shen, Jie; Zheng, Xinchun; Shen, Yi; et al. (Frontiers in Genetics, 2021)
Genome-wide association studies have>100 genetic risk or protective factors for rheumatoid arthritis. However, the reported genetic variants could only explain less than 40% heritability of rheumatoid arthritis. Majority of the heritability is still missing which require to be identified with more studies with different approaches and populations. In order to identify novel function SNPs to explain missing heritability and reveal novel mechanism pathogenesis of rheumatoid arthritis, 225 common SNPs located in miRNA and 4 HLA SNPs (HLA-DRB1, HLA-DRB9, HLA-DQB1 and TNFAIP3) which might influence the miRNA target binding or pre-miRNA stability were genotyped in 1,607 rheumatoid arthritis and 1,580 matched normal individuals. We identified 2 novel SNPs which were significant associated with rheumatoid arthritis including rs1414273 (miR-548ac, OR=0.84, P=8.26×10-4) and rs2620381 (miR-627, OR=0.77, P=2.55×10-3). In addition, we found individuals carried 8 risk alleles showed 15.38 (95%CI: 4.69-50.49, P<1.0x10-6) times more risk to be affected by RA. We also identified that rs5997893 (miR-3928) showed significant epistasis effect with rs4947332 (HLA-DRB1, OR=4.23, P=0.04) and rs2967897 (miR-5695) with rs7752903 (TNFAIP3, OR=4.43, P=0.03). Finally, we demonstrated targets of the significant miRNAs showed enrichment in immune related genes (P=2.0×10-5) and FDA approved drug target genes (P=0.014). Overall, 6 novel miRNA SNPs including rs1414273 (miR-548ac, P=8.26×10-4), rs2620381 (miR-627, P=2.55×10-3), rs4285314 (miR-3135b, P=1.10×10-13), rs28477407 (miR-4308, P=3.44×10-5), rs5997893 (miR-3928, P=5.9×10-3) and rs45596840 (miR-4482, P=6.6×10-3) were confirmed to be significantly associated with RA in a Chinese population. The risk of accumulative risk allele carriers significantly increased with the number of risk alleles. Our study suggest that miRNAs might be interesting targets to accelerate the understanding of the pathogenesis and drug development for rheumatoid arthritis.